Myocardial cytoprotection and ischemic myocardial dysfunction correction in stable angina patients after transluminal balloon angioplasty or coronary artery stenting - I. G. Gordeev; V. A. Lusov; E. A. Bekchiu; N. A. Volov; E. E. Ilina; A. Yu. Lebedeva (Российский кардиологический журнал, 2006)
The results of myocardial cytoprotection with mildronate and trimethazidine (Preductal MB) in stable angina patients with left ventricular (LV) myocardial dysfunction, including hibernation, are presented. All participants underwent transluminal balloon angioplasty. Mildronate and trimethazidine therapy was associated with decrease in local dyscontractility index and reduced s LV myocardial dysfunction. The latter, in its turn, was associated with improved cardiac pump function and decreased LV myocardial dysfunction.